FAKTOR-FAKTOR YANG MENYEBABKAN KESULITAN BELAJAR AKUNTANSI PADA SISWA MENENGAH ATAS DI MASA PANDEMI COVID-19 - Firda, Firda Alyang Luvita; Arifin, Zainal; Lukiani, Eunike Rose Mita (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research intended to describe the causes of high school students' difficulty learning accounting during the covid-19 pandemic. This study was implemented at 6 Public Senior High School Kediri. This research employed a descriptive qualitative method for data collection, including questionnaires for internal and external factors, interviews, and observations. According to the study, the causes of difficulty in learning accounting for high school students during the covid-19 pandemic fell into internal and external factors. The Internal factors consist of lack of confidence, lack of talent in calculating or analysing financial transactions, lack of interest, and lack of student motivation; on the other hand, the external factors include a less harmonious relationship and a lack of communication between children and parents, the way the teacher explained, the teacher relationship was not close to students due to the pandemic, boredom during online learning, unstable internet connection, friends who frequently invited students to play, and activities which were more engaging than studying accounting.